ANALISIS PENGARUH KUALITAS HIDUP DAN DUKUNGAN SOSIAL TERHADAP PRESTASI AKADEMIK MAHASISWA - Arina Nurrohmah; Ridho Pratama; David (Jurnal Binagogik, 2026)
This study examines the effects of quality of life and social support on students' academic achievement (measured by the most recent semester GPA). Data were collected from 50 university students (N=50) using a 26-item quality of life questionnaire and a 19-item social support questionnaire (Likert scale 1-5), along with GPA records. Multiple linear regression was performed using IBM SPSS Statistics 25 at a 5% significance level. The results indicate that quality of life and social support do not jointly predict academic achievement (F(2,47)=1.256; p=0.294), with R²=0.051. Individually, quality of life (b=0.0036; p=0.321) and social support (b=0.0015; p=0.616) are also non-significant predictors. These findings suggest that GPA variation in this sample is better explained by other factors beyond the two predictors. Future research should include additional variables (e.g., learning motivation, time management, and psychological factors) and use more diverse samples.